Emerging professional practices focusing on reducing inequity in speech-language therapy and audiology: a scoping review - Kristen Abrahams; Rizwana Mallick; Ameer S-J Hohlfeld; Thiani Pillay; Tamzyn Suliaman; Harsha Kathard (BMC, 2023)
Abstract Background For the professions of audiology and speech-language therapy (A/SLT), there continues be a dire need for more equitable services. Therefore there is a need to develop emerging practices which have a specific focus on equity as a driving force in shifting practices. This scoping review aimed to synthesise the characteristics of emerging practices in A/SLT clinical practice in relation to equity with an emphasis on communication professions. Methods This scoping review followed the Joanna Briggs Institute guidelines and aimed to map the emerging practices in A/SLT to identify the ways in which the professions are developing equitable practices. Papers were included if they addressed equity, focused on clinical practice and were situated within A/SLT literature. There were no time or language restrictions. The review included all sources of evidence across PubMed, Scopus, EbscoHost, The Cochrane Library and Dissertation Abstracts International, Education Resource Information Centre from their inception. The review uses PRISMA Extension for scoping reviews and PRISMA-Equity Extension reporting guidelines. Results The 20 included studies ranged from 1997-2020, spanning over 20 years. There were a variety of papers including empirical studies, commentaries, reviews and research. The results demonstrated that the professions were increasingly considering addressing equity through their practice. However, there was a prominent focus around culturally and linguistically diverse populations, with limited engagement around other intersections of marginalisation. The results also showed that while the majority of contributions to theorising equity are from the Global North with a small cluster from the Global South offering critical contributions considering social categories such as race and class. Collectively the contributions from the Global South remain a very small minority of the professional discourse which have a focus on equity. Conclusion Over the last eight years, the A/SLT professions are increasingly developing emerging practices to advance equity by engaging with marginalised communities. However, the professions have a long way to go to achieve equitable practice. The decolonial lens acknowledges the impact and influence of colonisation and coloniality in shaping inequity. Using this lens, we argue for the need to consider communication as a key aspect of health necessary to achieve health equity.